(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: The accepted standard of care for induction of lupus nephritis has been cyclophosphamide but recent trials suggest that mycophenolate mofetil may be more effective and less toxic. The objective of the study was to evaluate the patients achieving partial remission and complete remission after induction treatment of lupus nephritis by cyclophosphamide and mycophenolate mofetil. Materials and methods: It was a quasi-experimental study performed in the Department of Nephrology of Chittagong Medical college Hospital (CMCH). A total of 100 patients of lupus nephritis (Class III and IV) who fulfilled the designated criteria were enrolled in this study by nonprobability voluntary sampling method. The treatment was given on patient’s choice. After screening and treatment initiation, patients were assessed at 12 and 24 weeks. All the data were compiled in a structured case record form. Results: In the present study 48 patients (53.3%) in mycophenolate mofetil group and 42 patients (46.7%) in intravenous cyclophosphamide group completed 24 weeks of induction treatment of lupus nephritis. As per protocol analysis, 25(58.083%) of 48 patients in the MMF group and 7(16.7%) of 42 patients in intravenous cyclophosphamide group achieved complete remission at 24 weeks. Conclusion: Induction therapy with Mycophenolate mofetil was superior to intravenous cyclophosphamide in inducing complete emission of lupus nephritis in this study. JCMCTA 2020 ; 31 (2) : 104-109